Public Relations Strategy of the Ministry of Communication and Digital in the Use of Instagram Posts as a Medium for Disseminating Information - Farhan Fahrezi; Ayu Larasati (CV Edujavare Publishing, 2026)
This study examines the public relations (PR) strategy of the Ministry of Communication and Digital (Komdigi) of the Republic of Indonesia in utilizing official Instagram posts (@kemkomdigi) as a medium for public information dissemination and explores the causes of dominant negative public responses in the digital sphere. Using a constructivist paradigm and Robert K. Yin’s qualitative single-case study method, the study applies James E. Grunig and Larissa A. Grunig’s Relationship Management Theory and Four Models of Public Relations. Primary data were collected through in-depth interviews with key social media staff and management, observation of 24 selected posts and public comment threads from January to December 2025, and official documentation. The findings show that Komdigi’s PR strategy predominantly employs the Public Information and Two-Way Asymmetrical models. Information is verified through a multilayered process to ensure accuracy, while comment monitoring and monthly analytics guide message framing and content strategies. However, Two-Way Symmetrical communication remains constrained by bureaucratic hierarchies and public skepticism. The study recommends agile teams, streamlined response procedures, and empathy-driven narratives to strengthen digital public trust.